Maximum Output Power Tracking of Wind Turbine Using Intelligent Control - Muldi Yuhendri; Mochamad Ashari; Mauridhi Hery Purnomo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
The Output power of wind turbine is determined by wind speed. The Output power can be adjusted by controlling the generator speed and pitch angle of wind turbine. When the wind speed below the wind turbine rated, the output power of generator can be maximized by controlling the generator speed at point of maximum power coefficient. When the wind speed above the wind turbine rated, output power of wind turbine will exceed the power generators rated. In this condition, the output power of wind turbine needs to be regulated to conform to the generator power rate. Output power of wind turbine can be regulated by adjusting the pitch angle of wind turbine. In this paper is developed the control strategies based intelligent control for controlling the generator speed and pitch angle of wind turbine, so the  maximum output power tracking (MOPT) of wind turbine can be obtained at any wind speed variations. Generator speed is controlled using PI Fuzzy Logic Controller (PI-FLC) based Direct Field Oriented Control (DFOC). Pitch angle of wind turbine is controlled using Elman Recurrent Neural Network (RENN). The simulation results with Matlab Simulink shows that the both controller was successfully regulates the output power when the wind speed above the wind turbine rated and the output power can be maximum when the wind speed below the wind turbine rated.